2014
DOI: 10.4064/dm502-0-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid mixing of Swendsen–Wang dynamics in two dimensions

Abstract: We prove comparison results for the Swendsen-Wang (SW) dynamics, the heat-bath (HB) dynamics for the Potts model and the single-bond (SB) dynamics for the random-cluster model on arbitrary graphs. In particular, we prove that rapid (i.e. polynomial) mixing of HB implies rapid mixing of SW on graphs with bounded maximum degree and that rapid mixing of SW and rapid mixing of SB are equivalent. Additionally, the spectral gap of SW and SB on planar graphs is bounded from above and from below by the spectral gap of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 67 publications
(144 reference statements)
7
67
0
Order By: Relevance
“…Although our results are not as sharp as those discussed in [31], using the structure of the grid we are able to prove an upper bound on μ + which is close to the lower bound given in Proposition 2. Note that the toroidal L-grid has n := L 2 vertices.…”
Section: Theorem 27 Let G = (V E) Be a Connected Graph With N Versupporting
confidence: 64%
See 2 more Smart Citations
“…Although our results are not as sharp as those discussed in [31], using the structure of the grid we are able to prove an upper bound on μ + which is close to the lower bound given in Proposition 2. Note that the toroidal L-grid has n := L 2 vertices.…”
Section: Theorem 27 Let G = (V E) Be a Connected Graph With N Versupporting
confidence: 64%
“…2 )) and that rapid mixing occurs for finite grids when β is below this threshold; see [26] and Theorem 2.10 of [31]. It is conjectured that the Glauber dynamics mixes slowly when β is above this threshold; see Remark 2.11 of [31]).…”
Section: Comparison With Related Results and Phase Transitionsmentioning
confidence: 96%
See 1 more Smart Citation
“…For complete graphs, the mixing time is very well understood for all q ≥ 1 [20,1,11]. For Z 2 , for all q ≥ 1, the dynamics is fast mixing at all temperatures other than the critical one [26,27,2].…”
Section: The Weight W(σ) Of Configuration σ Is β M(σ) Where M(σ) Is Tmentioning
confidence: 99%
“…Long et al showed more refined results for the complete graph establishing that the mixing time is Θ(1) for β<normalβc, Θ(n1/4) for β=normalβc, and Θ(logn) for β>normalβc. For square boxes of 2, Ullrich proved that the mixing time of Swendsen‐Wang is polynomial for all temperatures (building upon results for the Glauber dynamics by Martinelli and Olivieri and Lubetzky and Sly ). Very recently, Guo and Jerrum showed that the mixing time of Swendsen‐Wang is polynomial for any graph G for all temperatures.…”
Section: Introductionmentioning
confidence: 99%